2013
DOI: 10.1111/jan.12112
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the diagnosis and management of tuberculosis: a focused ethnography of Somali patients and healthcare professionals in the UK

Abstract: Experiences of the diagnosis and management of tuberculosis: a focused ethnography of Somali patients and healthcare professionals in the UK. Abstract Aim.To explore experiences of the diagnosis and management of tuberculosis from the perspective of Somali patients and healthcare professionals involved in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 14 publications
1
69
0
Order By: Relevance
“…The presence in the household of long-term visitors from high incidence countries, lack of awareness about TB, stigma resulting in obstacles to access healthcare/treatment, and lack of willingness to disclose information about contacts could also play a part. There is evidence that stigma, fear of discrimination, social exclusion and deportation, and other sociocultural factors can be barriers to Somali patients accessing TB services and disclosing their TB status to facilitate contact tracing [1720], but less research has been performed on obstacles faced by other communities. Interestingly, we found that UK-born cases of South Asian ethnicity were more likely to be household transmitters compared to those born in South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The presence in the household of long-term visitors from high incidence countries, lack of awareness about TB, stigma resulting in obstacles to access healthcare/treatment, and lack of willingness to disclose information about contacts could also play a part. There is evidence that stigma, fear of discrimination, social exclusion and deportation, and other sociocultural factors can be barriers to Somali patients accessing TB services and disclosing their TB status to facilitate contact tracing [1720], but less research has been performed on obstacles faced by other communities. Interestingly, we found that UK-born cases of South Asian ethnicity were more likely to be household transmitters compared to those born in South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Since symptoms were attributed to causes for which participants would not ordinarily seek medical attention, such as drug and alcohol withdrawal, tiredness attributed to poor diet for economic reasons, and other long term conditions, indicates the ease with which serious illness can be missed by those living with complex health and social issues. For this reason, perhaps, the TB stigma reported in other studies as a barrier to health care [34] was not cited as a factor (although it was discussed in terms of a fear of disclosure of illness to others in the Somalian community by one Somali refugee). Our research supports the intensification of outreach initiatives to identify groups at risk of TB and the development of structured care pathways to support people into prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, when diagnosed with TB, patients will often hide the fact of the disease from others and, thus, isolate themselves to avoid negative public perceptions, disruption of work, and bringing shame to families and friends, which can have an impact on their physical, financial, social and mental health. These impacts are especially severe in terms of the maintenance of physical functions and emotions, and the occurrence of a mental illness, such as depression, can be found in as many as 70% of patients with TB (Doherty et al, 2013;Gerrish et al, 2013;Kibrisli et al, 2015;McArthur et al, 2016;Moya & Lusk, 2013;Murray et al, 2013;Zuñiga, Muñoz, Johnson, & Garcia, 2014).…”
Section: Objectivesmentioning
confidence: 99%
“…Research indicates that patients with TB often experience psychological distress, for example, stigma and depression, which adversely affects their ability to cope with stress, the side effects of treatment and daily life (Chang & Cataldo, ; Doherty et al., ; Duko, Gebeyehu, & Ayano, ; Gerrish, Naisby, & Ismail, ; Ige & Lasebikan, ; Masumoto et al., ; McArthur, Bali, & Khan, ; Moya & Lusk, ; Pan et al., ; Sagili, Satyanarayana, & Chadha, ; Shen et al., ; Singh, Pardal, & Prakash, ).…”
Section: Introductionmentioning
confidence: 99%